Are Downhill Varices an Overlooked Entity of Upper Gastrointestinal Bleedings?. (31st July 2018) - Ayvaz, M. A.; Rakici, H.; Allescher, H. D.
Abstract : Aim . Downhill varices are not so safe as thought and can lead to life-threating or mortal bleeding complication, even if rare. In order to draw attention to this topic, we analysed 129 patients. Materials and Methods . We evaluated the electronic endoscopy data records of all patients undergoing upper gastrointestinal endoscopy over a nine-year period from January 2004 till December 2012, within a retrospective approach. The primary endpoints, incidence, causes, kind of resulting upper gastrointestinal bleeding, and the severity of the bleeding were evaluated. Secondary endpoints were the evaluation of the size of downhill varices and a comparison of the risk of bleeding between downhill varices and uphill varices. Results . Downhill varices were identified, described, and/or documented in 129 patients of 25, 680 upper gastrointestinal endoscopies. 26 patients had central venous catheter or port implantation, 22 patients had a history of an implantation of a cardiac pacemaker, 7 patients had severe pulmonary artery embolism, and 4 patients had severe chronic obstructive pulmonary disease. Two patients had mediastinal tumors, and one patient had a large retrosternal goiter as a possible cause of the vena cava syndrome. Altogether, 62 patients were related to a vena cava superior syndrome; 67 were not. Conclusions . Downhill varices can be seen with an incidence of 0.5%. Therapeutic means are the banding therapy as a safe and effective option. Severe bleedings associated with downhill varices can be mortal. Severe forms of downhill varices should be examined in relation to the origin in order to start a specific therapy.